(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
By law or by statute. Belonging and autonomy in the legal experience of contemporary Italian Judaism ABSTRACT. The essay retraces the salient passages of the juridical condition of the Jews of Italy, from the second emancipation (1848) onwards, around the pivotal principles of community autonomy and individual belonging, which during the different eras - liberal, fascist, republican - have taken on different normative qualifications and consequent historical meanings. The historical perspective thus illustrates the unique and paradigmatic character of the Jewish case for the tension that has gradually been established between institutional reasons and individual demands, between the ’necessity’ of the community and the ’freedom’ of the Jews. From the reconstruction it emerges how, in the different moments, the initiative of the minority prevailed over the action of the State, mostly called upon to acknowledge the requests and solicitations of the Jewish leadership. SOMMARIO - 1. Premessa - 2. Tra emancipazione e tradizione. Modelli comunitari in età liberale - 3. Dal Consorzio delle Università israelitiche alla legge del 1930 - 4. L’autonomia confessionale. L’intesa con lo Stato e lo statuto dell’Unione delle Comunità ebraiche del 1987 - 5. Cenni conclusivi.